Studies on surface to bulk ionic mass transfer in bubble column - Verma A.K.; Rai S. (My University, 2025)
Mass-transfer coefficient with immersed surface of diameter 0.016 m placed axially in bubble column (internal diameter=0.0515m), was measured using electrochemical technique with ferro-ferricyanide system. Perforated-plate sparger (hole diameter=0.0015m) and single-nozzle spargers (hole diameter=0.001, 0.0015 and 0.002m) were used. Mass-transfer coefficient was found to be independent of initial bed height. It decreases as axial position of transfer surface from bottom increases at low gas velocities. The effect of type of sparger on mass-transfer coefficient was observed at all axial positions. It increases with increase in hole diameter for single-nozzle sparger. It is higher for perforated-plate distributor than that for single-nozzle sparger with same hole diameter. The present values are in comparison with data of Patil and Sharma [Chem. Eng. Res. Des. 61 (1983) 21]. Following correlation correlated present set of data: Stm=0.057(1-ε)(ReFr P=0.25> Sc2) -0.25. © 2003 Elsevier Science B.V. All rights reserved.